Geological structures control on earthquake ruptures: The Mw7.7, 2013, Balochistan earthquake, Pakistan. Issue 19 (9th October 2016) - Vallage, A.; Klinger, Y.; Lacassin, R.; Delorme, A.; Pierrot‐Deseilligny, M.
Abstract: The 2013 Mw 7.7 Balochistan earthquake, Pakistan, ruptured the Hoshab fault. Left‐lateral motion dominated the deformation pattern, although significant vertical motion is found along the southern part of the rupture. Correlation of high‐resolution (2.5 m) optical satellite images provided horizontal displacement along the entire rupture. In parallel, we mapped the ground rupture geometry at 1:500 scale. We show that the azimuth of the ground rupture distributes mainly between two directions, N216° and N259°. The direction N216° matches the direction of preexisting geologic structures resulting from penetrative deformation caused by the nearby Makran subduction. Hence, during a significant part of its rupture, the 2013 Balochistan rupture kept switching between a long‐term fault front and secondary branches, in which existence and direction are related to the compressional context. It shows unambiguous direct interactions between different preexisting geologic structures, regional stress, and dynamic‐rupture stress, which controlled earthquake propagation path. Key Points: High‐resolution quantification of the 2013 Balochistan earthquake displacement from optical image correlation Characterization of the frontal rupture geometry, based on 1:500 scale ground surface rupture mapping, inside the coseismic damage zone Preexisting geological structures and state of stress control on earthquake rupture propagation and geometrical complexities